Approachable accessibility planning for success - Dowden, Martine; Dowden, Michael (Apress, 2019)
"Understand the realities of modern web accessibility and what considerations should be made to include everyone. There are hundreds of millions of people who are being left out every single day on the web due to disability or circumstance. The purpose of web accessibility is to remove barriers and bring the information, services, and functionality of the web to as many people as possible so they can be included in this global community. This book makes the topic of web accessibility as approachable as possible to help every web professional become an accessibility advocate at their companies, on their projects, and in their communities. This discussion will go beyond the buzzword to explore the impact our designs and decisions have on real people, along with the ethical, legal, and financial incentives for accessibility prioritization. For those who are ready to get started the book covers tools and techniques for testing websites or web applications for conformance to the Web Content Accessibility Guidelines. Because we very rarely work in a vacuum the book also covers how to educate your team or company management on web accessibility as well as persuading them to invest time and money in accessibility. For those looking to start an accessibility practice at their company - or simply to ensure that nothing slips through the cracks - the book includes a guide to creating your very own accessibility action plan. Having a well-documented plan of action is an essential step in the long-term success of any initiative. Get started with web accessibility using Approachable Accessibility today."--Publisher's website